In this issue: Proteomics 2/2008 (Proteomics (Weinheim), 2008)
In this issue of Proteomics you will find the following highlighted articles: Particular particles pick out phosphopeptides promptly Phosphorylation/dephosphorylation is the most commonly used post‐translational signal in eukaryotic organisms. With a single site it might turn a pathway on or off, up or down; multiple site series can incrementally change the level of expression, effects can be direct or indirectly induced. Needless to say, phosphoproteins are extremely important subjects of study. Li et al. have developed a method for rapid collection and analysis of phosphopeptides: gallium oxide‐coated magnetic beads. Effective at very low phosphopeptide concentrations, a MALDI sample can be bound to the beads in 30 seconds. After a few washes, a small amount of the bead slurry is spotted on a MALDI plate, 2,5‐dihydroxybenzoic acid spotted as matrix, then, “Fire away!” The gallium oxide beads dramatically out perform silica‐Fe beads, Fe+3‐IMAC resin, and TiO2 beads. Li, Y. et al., Proteomics 2008, 8, 238–249. Plasma butyrylcholinesterase: multiple N‐glycan sites support multiple roles Cholinesterases have been of interest since their discovery in the early 1930’s. Acetylcholinesterase is the target of insecticides and nerve gases. Butyrylcholinesterase (BChE) plays a variety of roles because of its “relaxed” substrate requirements, able to detoxify heroin and aspirin as well as choline‐containing molecules. Of particular interest is its function as a scavenger of organophosphates to protect nerve‐associated acetylcholinesterase. Kolarich et al. explored the complexities of glycosylation of BChE, with 9 of 10 potential N‐glycosylation sites occupied in the 85 kDa protein. Of the variety of techniques applied to elucidating the glycan structures at particular sites, perhaps the most informative was porous graphitic carbon LC/MS. It yielded more information in 80 minutes than an overnight “classical” procedure. No evidence of O‐glycosylation or other post‐translational modifications were seen. Kolarich, D. et al., Proteomics 2008, 8, 254–263. DIGE digs up skeletal muscle fate The gradual loss of strength and muscle mass is a normal event in aging, measurable by published statistics for professional athletes, or by how long we take to push away from the table. Sarcopenia is the drastic form of muscle loss, resulting in severe impairment. Doran et al. selected the rat model of muscle mass loss between 3 months (young adult) and 30 months (old) to study, avoiding confounding human variables. Applying DIGE/MALDI‐TOF to gastrocnemius samples, they found 2493 spots, of which 69 exhibited dramatic up‐ or down‐regulation. The functional changes suggested by the quantitative changes included increased dependence on aerobic oxidative metabolism and fibre remodeling, probably due to impaired fibre repair. These findings were confirmed by Western blots and fluorescent confocal microscopy and concur with other published studies. Doran, P. et al., Proteomics 2008, 8, 364–377.